(3TQM bUjOI GdYQhSs - (3GdbfGU , NGdO Hf UahGfs
(3ChdgG (B:s
(3gPg GdbUjOg GdJi jSejgG GdYQH GdYQhS , bGd HYV Cgd GdCOH s
(3BNQgG (B:s
(3MdJ eRGeQge WGHJ eSGeQge YdJ YfGUQge ef bUQ YeQGf JeJ bUjOI GdYQhS HYhf Gdedc GdbOhS s
(3HBNQ UaMGJgG JYbjHIs
(3HGdeYgO fSNI CNQi GfXQ ai GdLRA GdChd Qbe (B545 (3COHs
(3bUjOg GdYQhS Ydi bGajg Gdfhf ddTGYQ NGdO Hf UahGf GdbfGU GdbGVi hgh TGYQ eZehQ jXf Cfg cGf ef YhGe GdUOQ GdChd GfXQg ai GdCYdGe (B296/2s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs